2023
DOI: 10.3390/brainsci13020200
|View full text |Cite
|
Sign up to set email alerts
|

Low Levels of Adenosine and GDNF Are Potential Risk Factors for Parkinson’s Disease with Sleep Disorders

Abstract: Sleep disturbances are the most prevalent non-motor symptoms in the preclinical stage of Parkinson’s disease (PD). Adenosine, glial-derived neurotrophic factor (GDNF), and associated neurotransmitters are crucial in the control of sleep arousal. This study aimed to detect the serum levels of adenosine, GDNF, and associated neurotransmitters and explored their correlations with PD with sleep disorders. Demographic characteristics and clinical information of PD patients and healthy participants were assessed. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…In rats, apigenin demonstrated GABAergic activity that was independent of GABA- benzodiazepine receptors and possibly mediated by the GABA A receptor ( 57 ). Apigenin also decreased levels of Tnf-α, Il-6, and iNos1 while maintaining elevated levels of Bdnf and glial Gdnf mRNA ( 77 , 78 ). Findings involving BDNF are interesting given that this protein was reported to be significantly lower in insomniac patients with short sleep duration ( 79 ).…”
Section: Apigenin and Sleepmentioning
confidence: 94%
“…In rats, apigenin demonstrated GABAergic activity that was independent of GABA- benzodiazepine receptors and possibly mediated by the GABA A receptor ( 57 ). Apigenin also decreased levels of Tnf-α, Il-6, and iNos1 while maintaining elevated levels of Bdnf and glial Gdnf mRNA ( 77 , 78 ). Findings involving BDNF are interesting given that this protein was reported to be significantly lower in insomniac patients with short sleep duration ( 79 ).…”
Section: Apigenin and Sleepmentioning
confidence: 94%
“…Additionally, it was found that GDNF along with adenosine rendered neuroprotection in PD patients with sleep disturbances. Low levels of GDNF were found in PD patients with more serious sleep related disorders . In another study, it was found that microencapsulation of GDNF led to sustained release in circulation for a much longer time.…”
Section: Novel Targets For Improved Pd Therapeuticsmentioning
confidence: 96%
“…Low levels of GDNF were found in PD patients with more serious sleep related disorders. 153 In another study, it was found that microencapsulation of GDNF led to sustained release in circulation for a much longer time. A single intrastriatal administration of microencapsulated GDNF was done in MTPT induced PD in monkeys.…”
Section: Glial Cell-line Derived Neurotrophic Factor (Gdnf)mentioning
confidence: 99%
“…Additional motor symptoms often seen in individuals with PD include impaired postural stability and reduced velocity of movement (Alfonsetti et al, 2022). PD is associated with other nonmotor symptoms, including cognitive impairment (dementia), mood disorders (depression), sensory abnormalities (restless legs), sensitivity to temperature changes, and gastrointestinal dysfunctions (Wang et al, 2023). Significant progress has been achieved by researchers in the exploration of therapeutic options for individuals Journal of Disability Research 2024 experiencing both motor and nonmotorized manifestations of PD despite the inherent incurability of this condition.…”
Section: Introductionmentioning
confidence: 99%